Performance Evaluation of Virtual Machine Monitors for Cloud Computing - Leite, Dionisio; Peixoto, Maycon; Santana, Marcos; Santana, Regina (Anais do Simpósio em Sistemas Computacionais de Alto Desempenho (SSCAD), 2012)
This paper presents a study about performance evaluation of virtualization technologies for cloud computing. Virtualization is the main technique in the cloud computing, although this approach demonstrates overhead in the host and some performance losses between the virtual machines. Aiming to verify the virtualization impacts, performance tests were realized between the virtual machine monitor and the host machine using the same workload. In addition, the number of virtual machines running concurrently, Xen and KVM, were analyzed to quantify the overhead of virtualization. Performance evaluation methodology was employed to planning the experiments. The results shows that virtualization shown overhead in relation to physical machine and the best responsive time was achieved by the KVM monitor.